The Comparison Between Balinese and Australian Swear Words in Terms of References Used - Putu Sidhi Mahayasa; I Gede Budasi; Rima Andriani Sari (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2026)
The objective of this research is to compare the references used in swear words in Balinese and Australian. Swear words are linguistically and culturally significant because they reflect social norms, beliefs, and emotional expression within a speech community. This research employed a comparative descriptive qualitative design using primary and secondary data. Primary data were obtained through semi-structured interviews with native Balinese speakers and native Australian English speakers, while secondary data were collected from relevant studies and academic documents. The data were analyzed through inductive categorization based on reference types in sociolinguistic studies of taboo language. The findings show that both languages share common reference domains, including religion/ supernatural being, sex, excrement, animals, personal background, mental illness, and sexual activity. However, Balinese swear words emphasize animal references, supernatural being, and social hierarchy, whereas Australian English swear words more frequently involve sexual references and personal insults used flexibly in informal contexts. These differences reflect distinct sociocultural values and potential sources of cross-cultural misunderstanding. For the implication of this study is the importance of understanding these similarities and differences for preventing cross-cultural misunderstanding and for promoting effective intercultural communication, particularly between speakers of Balinese and Australian English.